2016
DOI: 10.1016/j.toxrep.2016.04.001
|View full text |Cite
|
Sign up to set email alerts
|

Safety assessment of a standardized polyphenolic extract of clove buds: Subchronic toxicity and mutagenicity studies

Abstract: Despite the various reports on the toxicity of clove oil and its major component eugenol, systematic evaluations on the safety of polyphenolic extracts of clove buds have not been reported. Considering the health beneficial pharmacological effects and recent use of clove polyphenols as dietary supplements, the present study investigated the safety of a standardized polyphenolic extract of clove buds (Clovinol), as assessed by oral acute (5 g/kg b.wt. for 14 days) and subchronic (0.25, 0.5 and 1 g/kg b.wt. for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(29 citation statements)
references
References 30 publications
2
27
0
Order By: Relevance
“…Hoseini et al (2011) used 300, 500, and 700 mg/L of CLP and observed no effect on serum levels of AST, ALT, and ALP in beluga sturgeon (Huso huso). Moreover, Vijayasteltar et al (2016) reported that CLP inclusion at 0.25, 0.50, and 1.0 g/kg in the diet of rats did not affect AST, ALT, and ALP activity. In another study, Velisek et al (2005) used clove oil at 0.3, 0.5, 0.7, 0.9, and 1.1 g/L and reported unchanged AST, ALT, and ALP in carp.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…Hoseini et al (2011) used 300, 500, and 700 mg/L of CLP and observed no effect on serum levels of AST, ALT, and ALP in beluga sturgeon (Huso huso). Moreover, Vijayasteltar et al (2016) reported that CLP inclusion at 0.25, 0.50, and 1.0 g/kg in the diet of rats did not affect AST, ALT, and ALP activity. In another study, Velisek et al (2005) used clove oil at 0.3, 0.5, 0.7, 0.9, and 1.1 g/L and reported unchanged AST, ALT, and ALP in carp.…”
Section: Resultsmentioning
confidence: 97%
“…The European Union (EU) issued a ban on the use of antibiotics in animal feed in 2006 (Belal et al, 2018). However, researchers contend that herbs, medicinal plants and spices may be alternatives to antibiotics for promoting animal health (Vijayasteltar et al, 2016;Al-Shammari et al, 2017). Cloves, cardamom, anise, ginger, black pepper, and cumin are a group of aromatic plants that are used widely due to their positive effects on growth and health of poultry, probably as a result of their immune stimulatory properties (Chowdhury et al, 2018;Kunnumakkara et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Food and Drug Administration (FDA) has confirmed the safety of clove buds, clove oil, eugenol, and oleoresins as a food supplement; however, there has been considerable attention regarding its toxicity recently [123]. Prashar et al [21] have examined the cytotoxic activities of CEO and eugenol in vitro against human fibroblasts and endothelial cells, and they documented they recognized them as safe.…”
Section: Toxicity Dosesmentioning
confidence: 99%
“…Given the similarity of Oligopin® to other FMPBE, it is considered reasonable to assume that Oligopin® would have similar properties for each of these toxicological endpoints. It is also of interest to compare the toxicity of Oligopin® with that of proanthocyanidins extracted from grape seeds [ 21 ], and Clovinol, a standardized polyphenolic extract of clove buds [ 25 ], which are also used as nutritional supplements.…”
Section: Discussionmentioning
confidence: 99%